Are all student evaluation scores created equally? Identifying factors that hospitality administrators should consider when assessing student feedback. (June 2020) - Dawson, Mary; DeFranco, Agnes; Draper, Jason
Abstract: Hospitality program administrators must evaluate faculty on their perceived level of that faculty's teaching effectiveness. Interpreting student evaluation ratings is the most frequently used method of assessing faculty performance. This study examines factors that potentially should be taken into consideration while assessing student evaluation scores. Evaluation scores ( n = 4893) were analyzed for one academic year. The findings show a relationship between class size, grade distribution, and teaching experience with student ratings of faculty. The results also discovered that student ratings were significantly higher for courses that required a laboratory component and near significantly higher for elective vs. required courses.